THE SCHOLAR’S SELFLESS DEVOTION: VOLODYMYR KACHKAN – 75! - Sloniovska, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article conducts a review of Academician Volodymyr Kachkan’s creative accomplishments, carries out an evaluation of his creative achievements and scientific interests.